P318 Ustekinumab: early experience and medium-term outcomes from a UK multi-centre real-world cohort. (25th January 2019) - Gadhok, R; Rao, R; Honap, S; Samaan, M; Harpham-Lockyer, L; Kwok, H; Whitley, L; Ibarra, A; Burgess, N; Seward, E; Parkes, G; Mehta, S; et al.
Abstract: Background: Ustekinumab is effective in inducing and maintaining remission of Crohn's disease (CD) in clinical trials. We present the first UK real-world, multi-centre study of effectiveness. Methods: Data were collected for patients started on ustekinumab for CD from September 2015 to May 2018 at 3 tertiary London centres. Clinical endpoints were (i) remission (Harvey–Bradshaw Index (HBI) ≤4 points) and (ii) response (reduction in HBI of ≥3 points or sustained HBI ≤ 4 points) at Week 8 and 32. Biological endpoints were (i) remission (CRP < 5 mg/l in patients with a baseline CRP >5 mg/l) and (ii) response (50% reduction in CRP) at Weeks 8 and 32. Results: Baseline characteristics of the 149 patients analysed are shown in Table 1. The majority (146 (98%)) had failed anti TNF therapy. All patients received i.v. induction and 147 (99%) received a s.c. dose at Week 8. At Week 32, 91 (75.8%) patients were on 8 weekly dosing. Discontinuation occurred in 24 (16.1%) patients due to: primary non-response (14 (9.4%)), drug reactions (2 (1.3%)), side effects (2 (1.3%)), and other causes (6 (4.0%)). Follow-up to Week 32 was available for 125 (83.8%) patients. Clinical and biological outcomes at Week 8 and 32 are shown in Figure 1. Clinical and biological outcomes at Weeks 8 and 32. Adverse events occurred in 16 (10.7%) patients. Dosing schedule did not impact clinical and biological outcome at Week 32. Where paired data were available, mean (SD) HBI decreased significantly from baseline (6.2(4.9)) to Week 8 (4.6 (4.4), n = 99, p = 0.016) and was sustained at Week 32 (4.7 (4.1), n = 56, p < 0.001). Mean (SD) CRP decreased significantly from baseline (18.1 mg/l (21.9)) to Week 8 (11.9 mg/l (17.2), n = 122, p = 0.002), but did not sustain significant improvement at Week 32 (12.9 mg/l (17.4), n = 93, p = 0.158). Clinical remission at Week 8 was significantly associated with remission at Week 32: clinical remission ( n = 34, p = 0.013, RR 3.16, 95% CI 1.23–8.13), and biological remission ( n = 56, p = 0.027, RR 1.95, 95% CI 1.21–3.13). Biological remission at Week 8 was significantly associated with outcome at Week 32: biological response ( n = 62, p = 0.003, RR 4.72, 95% CI 0.65–13.51), and biological remission ( n = 62, p = 0.003, RR 4.41, 95% CI 1.78–10.87). Conclusions: Ustekinumab is effective in a real-world cohort with response sustained at 6 months. Clinical and biological remission at Week 8 predicted both clinical and biological outcomes at Week 32.